Ecotrophic perspective in fisheries management: a review of Ecopath with Ecosim models in European marine ecosystems - Keramidas, Ioannis; Dimarchopoulou, Donna; Ofir, Eyal; Scotti, Marco; Tsikliras, Athanassios C.; Gal, Gideon (Frontiers in Marine Science, 2023)
The aim of this work is to present the food web models developed using the Ecopath with Ecosim (EwE) software tool to describe structure and functioning of various European marine ecosystems (eastern, central and western Mediterranean Sea; Black Sea; Bay of Biscay, Celtic Sea and Iberian coast; Baltic Sea; North Sea; English Channel, Irish Sea and west Scottish Sea; and Norwegian and Barents Seas). A total of 177 Ecopath models based on 154 scientific publications, which report original, updated and modified versions, were reviewed. Sixty nine models included Ecosim temporal simulations while 24 implemented Ecospace spatiotemporal dynamics. Most of the models and publications referred to the English Channel, Irish Sea and west Scottish Sea sub-regions, followed by the Bay of Biscay, Celtic Sea and Iberian coast. In the Mediterranean Sea, the western region had the largest number of models and publications, followed by the central and eastern regions; similar trends were observed in previous literature reviews. Most models addressed ecosystem functioning and fisheries-related hypotheses while several investigated the impact of climate change, the presence of alien species, aquaculture, chemical pollution, infrastructure, and energy production. Model complexity (i.e., number of functional groups) increased along the time series. Main forcing factors considered to run spatial and temporal simulations were trophic interactions, fishery, and primary production. Average scores of ecosystem indicators derived from the Ecopath summary statistics were compared. Uncertainty was also investigated based on the use of the Ecosampler plug-in and the Monte Carlo routine; only one third of the reviewed publications incorporated uncertainty analysis. Only a limited number of the models included the use of the ECOIND plug-in which provides the user with quantitative output of ecological indicators. We assert that the EwE modelling approach is a successful tool which provides a quantitative framework to analyze the structure and dynamics of ecosystems, and to evaluate the potential impacts of different management scenarios.